1993
DOI: 10.1142/s0217979293003218
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Space Formulation of Quantum State Functions

Abstract: Allowing for virtual paths in phase space permits an extension of Hamilton’s principle of least action, of lagrangians and of hamiltonians to phase space. A subsequent canonical quantization, then, provides a framework for quantum statistical mechanics. The classical statistical mechanics and the conventional quantum mechanics emerge as special case of this formalism. Von Neumann’s density matrix may be inferred from it. Wigner’s functions and their evolution equation may also be obtained by a unitary transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…It can be easily shown that the Wigner representation can be obtained by a canonical transformation or by the corresponding unitary transformation in the EPS [11]. The same technique could be applied to obtain the Wigner equation from the Schrödinger equation in the phase space [16] showing the relation between the EPS technique and the Later one.…”
Section: Becomes [15]mentioning
confidence: 95%
See 3 more Smart Citations
“…It can be easily shown that the Wigner representation can be obtained by a canonical transformation or by the corresponding unitary transformation in the EPS [11]. The same technique could be applied to obtain the Wigner equation from the Schrödinger equation in the phase space [16] showing the relation between the EPS technique and the Later one.…”
Section: Becomes [15]mentioning
confidence: 95%
“…The canonical transformations that leaves the extended Hamilton equations form invariant are the extended canonical transformations [11]. Let us consider the following linear transformation…”
Section: The Extended Canonical Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the arguments invoked on the basis of the Heisenberg uncertainty principle made the physical meaning of the "phase space points" problematic, things have changed and phase space techniques mainly formulated by the theory of deformation quantization [23] and a family of Schrödinger equations in phase space [24,25,26,27,28] are now widely accepted and used. As an approach of the latter type, Sobouti and Nasiri [29] have proposed a formulation of quantum statistical mechanics by generalizing the principle of least action to the trajectories in phase space, and a canonical quantization procedure in this space. In the extended phase space (EPS) formalism, positions and momenta are assumed to be independent c-number variables.…”
Section: Introductionmentioning
confidence: 99%